2022
DOI: 10.1136/bmjopen-2022-063525
|View full text |Cite
|
Sign up to set email alerts
|

How missing evidence-based medicine indicators can inform COVID-19 vaccine distribution policies: a scoping review and calculation of indicators from data in randomised controlled trials

Abstract: ObjectiveReports of efficacy, effectiveness and harms of COVID-19 vaccines have not used key indicators from evidence-based medicine (EBM) that can inform policies about vaccine distribution. This study aims to clarify EBM indicators that consider baseline risks when assessing vaccines’ benefits versus harms: absolute risk reduction (ARR) and number needed to be vaccinated (NNV), versus absolute risk of the intervention (ARI) and number needed to harm (NNH).MethodsWe used a multimethod approach, including a sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Therefore, guiding the distribution of COVID-19 vaccines based on public statistical data should be of particular interest for governments, all the more so as there were countries that purchased a much larger number of vaccine doses (Australia, Canada, Great Britain) and later, they had to redistribute or donate them to other countries in need [ 78 ]; there were also situations where vials were wasted for various reasons [ 79 , 80 ]. Several studies clearly emphasize that the access to COVID-19 vaccines is facilitated by favorable socio-economic conditions [ 81 ], and the priority target group in obtaining them should be the population at major risks [ 82 , 83 ]. Thus, low-income countries should be generously supported to reach a significant immunization threshold and to have an equitable vaccination so that marginalized groups are not extremely affected [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, guiding the distribution of COVID-19 vaccines based on public statistical data should be of particular interest for governments, all the more so as there were countries that purchased a much larger number of vaccine doses (Australia, Canada, Great Britain) and later, they had to redistribute or donate them to other countries in need [ 78 ]; there were also situations where vials were wasted for various reasons [ 79 , 80 ]. Several studies clearly emphasize that the access to COVID-19 vaccines is facilitated by favorable socio-economic conditions [ 81 ], and the priority target group in obtaining them should be the population at major risks [ 82 , 83 ]. Thus, low-income countries should be generously supported to reach a significant immunization threshold and to have an equitable vaccination so that marginalized groups are not extremely affected [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ndings of another prospective cohort study using international data revealed that 70year-old patients and older ones requiring cancer and non-cancer surgery had more desirable (i.e., lower) NNVs to prevent mortality than the general population. Since the NNV statistic is highly associated with the incidence and prevalence of the disease of interest, this suggests the more favorable NNVs among subpopulations at higher risk of morbidity and mortality from the COVID-19 disease (7,16). These were consistent with the recommendations by the US Centers for Disease Control and Prevention and Public Health England in which they suggested that vulnerable individuals for morbidity and mortality from the COVID-19 disease should be in the frontline of receiving the vaccine (17).…”
Section: Discussionmentioning
confidence: 99%
“…In a commentary, the NNVs of 78, 81, 84, 108, and 119 were reported respective to the types of vaccines, namely AstraZeneca-Oxford, Moderna-NIH, Johnson & Johnson, Gamaleya, P zer-BioNTech. Moreover, NNV variations could be attributable to the differences in location, time, target groups, SARS-CoV-2 variant, and et cetera (7,8).…”
Section: Introductionmentioning
confidence: 99%